PEMANFAATAN TEKNOLOGI LOCATION BASED SERVICE (LBS) UNTUK INFORMASI DAN PENCARIAN WILAYAH PERIKANAN DI BENGKULU SELATAN - Ardi Wijaya; Chahima Gustina (JSAI (Journal Scientific and Applied Informatics), 2021)
Technological developments rapidly and affect of changes in human lifestyle. The demand of it is increasingly sophisticated technology that cause humans create tools that facilitate human work. One of them is searching location by using GPS (Global Positioning System). It determines the user's location by using Location Based Service. It is expected to overcome the problem of user in searching location. This paper discusses the user searches location by using Location Based Service. Through the help of Location Based Service will be pinned and will help to determine where the location of a user to their android based smartphones. The results can be obtained from the User Acceptance Test (UAT). It has a percentage of 80% of the 20 users performed. Furthermore, it is not appropriate to have a percentage of  20%  of  20 peers. Keywords:Location Based Services, Global  Positioning System (GPS) Android